Preparation of peptide–MHC and T-cell receptor dextramers by biotinylated dextran doping - Michael T. Bethune; Begoña Comin-Anduix; Yu-Hsien Hwang Fu; Antoni Ribas; David Baltimore (BioTechniques)
Peptide–major histocompatibility complex (pMHC) multimers enable the detection, characterization, and isolation of antigen-specific T-cell subsets at the single-cell level via flow cytometry and fluorescence microscopy. These labeling reagents exploit a multivalent scaffold to increase the avidity of individually weak T-cell receptor (TCR)-pMHC interactions. Dextramers are an improvement over the original streptavidin-based tetramer technology because they are more multivalent, improving sensitivity for rare, low-avidity T cells, including self/tumor-reactive clones. However, commercial pMHC dextramers are expensive, and in-house production is very involved for a typical biology research laboratory. Here, we present a simple, inexpensive protocol for preparing pMHC dextramers by doping in biotinylated dextran during conventional tetramer preparation. We use these pMHC dextramers to identify patient-derived, tumor-reactive T cells. We apply the same dextran doping technique to prepare TCR dextramers and use these novel reagents to yield new insight into MHC I–mediated antigen presentation.